The Economic Effects of Constitutions: Do Budget Institutions Make Forms of Government More Alike? - Martin Ardanaz; Carlos Scartascini (Inter-American Development Bank (IDB), 2013)
According to an influential theoretical argument, presidential systems tend to present smaller governments because the separation between those who decide the size of the fiscal purse and those who allocate it creates incentives for lower public expenditures. In practice, forms of government vary greatly, and budget institutions -the rules according to which budgets are drafted, approved, and implemented- are one (of many) drivers of such variation. This paper argues that under more hierarchical budget rules, presidential and parliamentary systems generate a similar incentive structure for the executive branch in shaping the size of government. This hypothesis is tested on a broad cross-section of countries, presidentialism is found to have a negative impact on government size only when executive discretion in the budget process is low (that is, in a context of separation of powers). However, the negative effect of presidentialism on expenditures vanishes or is even reversed when the executive`s discretion over the budget process is higher. Hence, budget institutions that impose restrictions on the legislature`s ability to amend budget proposals can make political regimes look more alike in terms of fiscal outcomes.
Keywords: D72; D78; H61; 330